Developing the microbial consortium to enhance the performance of granular sludge in anaerobic sequencing batch reactors (ASBR) treating glycerol - Dinh Thi Nga (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
Granular sludge from a full-scale methane reactor treating brewery wastewater was used as a seed for the treatment of glycerol in a laboratory-scale anaerobic sequencing batch reactor (ASBR) and the change in the microbial community during the acclimation stages was examined. Two types of substrate solutions, a glucose, sodium acetate, and lactic acid mixture, as well as glycerol were prepared and fed by mixing the two solutions. The glycerol part of the influent total (COD) was increased stepwise from 0% to 100% while keeping the COD loading rate at 2.5 g COD/L/d throughout the fermentation process. Vigorous methane gas production, ca 0.58L CH4/L/d, occurred during the acclimation stages. Microbial analysis revealed that both bacterial and archaeal communities changed significantly. Bacteria of the genus Trichococcus and family Syntrophomonadaceae became dominant rapidly after acclimation began, and archaea belonging to the hydrogenotrophic methanogens of the genera Methanobacterium and Methanospirillum increased during acclimation. The performance of the seed sludge enriched with glycerol acclimated granular sludge, i.e. containing the functional microorganisms, were determined at two feeding strategies: case 1 (gradually increasing glycerol in the influent) and case 2 (high glycerol concentration from the start, day 1). Four identical reactors were operated for 25 days at the same conditions of OLR, HRT and temperature. The two reactors were seeded with a mixture of beer brewery sludge and that containing FMO from glycerol acclimation runs while two reactors contained only beer brewery seed sludge. In each pair, one was run as case 1, in which glucose, acetic acid and lactic acid were part of the start-up substrate, and the other was run as case 2. The performance of the reactors seeded with glycerol-grown seed sludge (G1 and G2) was much better than those seeded with only brewery wastewater grown sludge (B1 and B2) in terms of biogas production rate (GPR), methane production rate (MPR) and methane yield. In the run at gradually increasing glycerol concentration in the influent, the average MPR of G1 was 1 L-biogas/L/d at the early stage and 0.9 L-biogas/L/d at the 25th day. Run B1 has MPR of 0.3 L-biogas/L/d at earlier period of start-up and 0.7L-biogas/L/d at the last week of run. Feeding the reactor at start up with easily degradable substrate and gradually increasing glycerol showed better GPR, MPR and methane yield than when reactor was fed with only glycerol as substrate from day 1. The latter also showed higher VFA levels especially during the earlier period of start-up. The performance was worse without glycerol-grown seed sludge (B1 vs G1 and B2 vs G2) and with feeding of glycerol as 100% of total influent COD from day 1. The best performance was achieved in the reactor that was inoculated with sludge acclimated and grown on glycerol and fed with gradually increasing glycerol portion during start-up.
Thesis (Ph. D. Environmental Engineering)--University of the Philippines, Diliman
Keywords: Sewage -- Purification -- Microbial granulation process; Sewage -- Purification -- Sequencing batch reactor process